Emerging therapies in the management of Irritable Bowel Syndrome (IBS). (2nd January 2022) - Elwing, Jill E.; Atassi, Hadi; Rogers, Benjamin D.; Sayuk, Gregory S.
ABSTRACT: Introduction: Irritable bowel syndrome (IBS) is a symptom-based disorder of chronic abdominal pain and altered bowel habits. The pathogenesis of IBS is multifactorial, leading to the potential for the development of diverse treatment strategies. This mechanistic heterogeneity suggests that available therapies will only prove effective in a subset of IBS sufferers. Current US Food and Drug Administration (FDA) approved therapies for IBS with diarrhea (IBS-D) and IBS with constipation (IBS-C) are reviewed. Limited symptom responses and side effect experiences lead to considerable patient dissatisfaction with currently available IBS treatments. Only a small percentage of IBS patients are on prescription therapies underscoring the potential market and need for additional therapeutic options. Areas covered: Expanding on currently available therapies, the serotonergic and endogenous opioid receptor systems continue to be a focus of future IBS treatment development. Additional novel emerging therapies include the endogenous cannabinoid system, bile acid secretion and sequestration, and exploit our enhanced understanding of visceral sensory signaling and intestinal secretomotor function. Expert opinion: While challenges remain for the future development of IBS therapies, the diverse etiologies underlying the disorder present an opportunity for novel therapies. Hence, great potential is anticipated for future IBS treatment options.